On the way to the next monetary crisis - Karlheinz Kleps (Intereconomics, 1972)
The euphorla felt after the monetary decisions in Washington was Justified. A trade war on the international level had seemed to be in the offing and was avoided. With the Immediate threat thus averted, a lasting solution of all monetary problems however is still not in sight.
Keywords: 330; Monetary Policy